Development of a multimedia information kiosk for public libraries. - Sunita Kumari. (2008)
The aim is to introduce an interactive communication medium by developing a multimedia information kiosk that contains the information about the library services, pragrammes and activities. A prototype multimedia information kiosk using Macromedia Directorwas developed and evaluated to seek the feedback and response of the library patrons.